2022
DOI: 10.1038/s41598-022-15742-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of critically endangered Dactylorhiza hatagirea (D. Don) Soo from North-Western Himalayas and implications for conservation

Abstract: Dactylorhiza hatagirea (D. Don) Soo is medicinally important herb, which is widely used in ayurveda, unani, and folk/traditional medicine system to cure diseases. Due to its immense ethno-botanical properties, the trade of D. hatagirea is estimated to be USD 1 billion/year in India. Unfortunately, due to overexploitation of the herb from the wild, has resulted in dwindling of its populations in their natural habitats, which has led to its critically endangered status. Molecular genetic studies are still scarce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In addition, ferulic acid is known to play a role in drought tolerance by increasing lipid peroxidation through the activation of antioxidant enzymes and by increasing proline and soluble sugar content in cucumber leaves [20]. These data, together with the differential accumulation of TPC and TFC, provide further evidence that phenolic compounds play important physiological and biochemical roles in plant cells, particularly in ameliorating abiotic stress [27].…”
Section: Discussionmentioning
confidence: 79%
“…In addition, ferulic acid is known to play a role in drought tolerance by increasing lipid peroxidation through the activation of antioxidant enzymes and by increasing proline and soluble sugar content in cucumber leaves [20]. These data, together with the differential accumulation of TPC and TFC, provide further evidence that phenolic compounds play important physiological and biochemical roles in plant cells, particularly in ameliorating abiotic stress [27].…”
Section: Discussionmentioning
confidence: 79%
“…Roads have played a crucial role in human activities throughout the agricultural development and urbanization process, negatively impacting the genetic diversity and differentiation of wild plant populations [9], by reducing plant diversity and limiting certain species [10]. Orchids, one of the most sensitive plants in nature, suffer from habitat fragmentation due to indiscriminate mining and overexploitation [11][12][13], resulting in changes in their genetic structure and reduced genetic diversity. An evaluation of 653 orchid species in China revealed that 65% of these species face challenges related to habitat fragmentation [14].…”
Section: Introductionmentioning
confidence: 99%